Matching models and housing markets: the role of the zero-profit condition - Gaetano Lisi (Economics and Econometrics Research Institute (EERI), 2012)
The recent and growing literature which has extended the use of search and matching models even to the housing market does not use the free entry or zero-profit assumption as a key condition for solving the equilibrium of the model. This is because a straightforward adaptation of the basic matching model to the housing market seems impossible. However, this paper shows that the zero-profit condition can be easily reformulated to take the distinctive features of the housing market into account. Indeed, it helps to provide a theoretical explanation for well-known empirical regularities in the housing markets.
Keywords: 330